2002
DOI: 10.1046/j.1365-2567.2002.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Products from human mast cell line cells enhance the production of interferon‐γ by CD8+ and CD4+ T cells

Abstract: SUMMARYIn patients with allergic asthma, T-cell cytokines are implicated in the regulation of the local inflammation in the airways. The ability of sensitized mast cells to release mediators and cytokines early upon allergen stimulation makes them important candidates for local immunoregulation. We have studied the effects of human mast cells on T cells with the use of the human mast cell line HMC-1. We showed that activated human mast cells or their soluble products induced and enhanced the interferon-c (IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Still, there is a hypothesis that Th1 cells are associated with the stable lesion – gingivitis – while a Th2 response is linked to disease progression – periodontitis (Gemmell et al , 2002). The notion of a functional relationship between mast cells and T lymphocytes has been strengthened as activated mast cells reside in close apposition to T cells in some inflammatory processes (Bhattacharyya et al , 1998; Mekori and Metcalfe, 1999) and mast cells can secrete both Th2‐type (De Pater‐Huijsen et al , 1997; Hültner et al , 2000; Coulombe et al , 2002; De Pater‐Huijsen et al , 2002) and Th1‐type (Metcalfe et al , 1997; Tkaczyk et al , 2000) cytokines, influencing the differentiation of T cells (Robinson et al , 1993; Huels et al , 1995). Nevertheless, mast cells seem to be able to present antigens to T cells in vitro (Fox et al , 1994; Love et al , 1996; Malaviya et al , 1996; Villa et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Still, there is a hypothesis that Th1 cells are associated with the stable lesion – gingivitis – while a Th2 response is linked to disease progression – periodontitis (Gemmell et al , 2002). The notion of a functional relationship between mast cells and T lymphocytes has been strengthened as activated mast cells reside in close apposition to T cells in some inflammatory processes (Bhattacharyya et al , 1998; Mekori and Metcalfe, 1999) and mast cells can secrete both Th2‐type (De Pater‐Huijsen et al , 1997; Hültner et al , 2000; Coulombe et al , 2002; De Pater‐Huijsen et al , 2002) and Th1‐type (Metcalfe et al , 1997; Tkaczyk et al , 2000) cytokines, influencing the differentiation of T cells (Robinson et al , 1993; Huels et al , 1995). Nevertheless, mast cells seem to be able to present antigens to T cells in vitro (Fox et al , 1994; Love et al , 1996; Malaviya et al , 1996; Villa et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…17 Thus our results suggest a specific link between mast cell activation and IFN-c secretion by CD4+/ CD8+ T cells, as described in vitro. 33 Mast cells also release nerve growth factor which can play a role in the stress induced increase in CPP. 34 A 2-3 day delay has already been described in vitro for the effects of IFN-c on T84 cells to decrease levels of ZO-1 and to alter apical actin organisation, which leads to disorganisation of TJs and increased permeability.…”
Section: Role Of Mast Cells and Ifn-cmentioning
confidence: 99%
“…Con-3 2.7 ϫ 10 sequently, CAEBV infection was considered to be the cause of his symptoms. Using fluorescence-activated cell sorting procedures, as described elsewhere [11], we demonstrated that the EBV load was confined to the natural killer cell compartment, and the patient was treated with high-dose dexamethasone, etoposide, and cyclosporine, followed by nonmyeloablative, allogeneic hematopoietic stem cell transplantation (HSCT) after induction with fludarabine and total body irradiation [12]. After an initial favorable response, EBV load rapidly increased (figure 1), and the patient developed severe electrolyte disturbances and thrombocytopenia.…”
mentioning
confidence: 99%
“…A high EBV load of copies/mL was measured 6 15.0 ϫ 10 in the peripheral blood by quantitative PCR. Using cell sorting techniques [11], the EBV load was found to be located in the natural killer cell compartment. Bone marrow aspirate and biopsy results indicated hypercellular marrow with a reactive inflammatory response and hemophagocytosis.…”
mentioning
confidence: 99%